American Time Use Survey, 2005 ([Verlag nicht ermittelbar], 2007)
The American Time Use Survey (ATUS) collects information on how people living in the United States spend their time. Data collected in this study measured the amount of time that people spent doing various activities in 2005, such as paid work, child care, religious activities, volunteering, and socializing. Respondents were randomly selected from households that had completed their final month of the Current Population Survey (CPS), and were interviewed two to five months after their household's last CPS interview. Respondents were interviewed only once and reported their activities for the 24-hour period from 4 a.m. on the day before the interview until 4 a.m. on the day of the interview. Respondents indicated the total number of minutes spent on each activity, including where they were and whom they were with. Except for secondary child care, data on activities done simultaneously with primary activities were not collected. Part 1, Respondent and Activity Summary File, contains demographic information about respondents and a summary of the total amount of time they spent doing each activity that day. Part 2, Roster File, contains information about household members and nonhousehold children under the age of 18. Part 3, Activity File, includes additional information on activities in which respondents participated, including the location of each activity and the total time spent on secondary child care. Part 4, Who File, includes data on who was present during each activity. Part 5, ATUS-CPS 2005 File, contains data on respondents and members of their household collected two to five months prior to the ATUS interviews during their participation in the Current Population Survey (CPS). Parts 6-10 contain supplemental data files that can be used for further analysis of the data. Part 6, Case History File, contains information about the interview process, such as identifiers and interview outcome codes. Part 7, Call History File, gives information about each call attempt, including the call date and outcome. Part 8, Trips File, provides information about the number, duration, and purpose of overnight trips away from home for two or more nights in a row. Part 9, Replicate Weights File I, contains base weights, replicated base weights, and replicate final weights for each case that was selected to be interviewed for ATUS, while Part 10, Replicate Weights File II, contains replicate weights that were generated using the 2006 weighting method. Demographic variables include sex, age, race, ethnicity, education level, income, employment status, occupation, citizenship status, country of origin, relationship to household members, and the ages and number of children in the household.